Neuromagnetic Oscillations Predict Evoked-Response Latency Delays and Core Language Deficits in Autism Spectrum Disorders - Edgar, J. Christopher; Khan, Sarah Y.; Blaskey, Lisa; Chow, Vivian Y.; Rey, Michael; Gaetz, William; Cannon, Katelyn M.; Monroe, Justin F.; Cornew, Lauren; Qasmieh, Saba; Liu, Song; Welsh, John P.; et al. (Journal of autism and developmental disorders, 2015)
Previous studies have observed evoked response latency as well as gamma band superior temporal gyrus (STG) auditory abnormalities in individuals with autism spectrum disorders (ASD). A limitation of these studies is that associations between these two abnormalities, as well as the full extent of oscillatory phenomena in ASD in terms of frequency and time, have not been examined. Subjects were presented pure tones at 200, 300, 500, and 1,000 Hz while magnetoencephalography assessed activity in STG auditory areas in a sample of 105 children with ASD and 36 typically developing controls (TD). Findings revealed a profile such that auditory STG processes in ASD were characterized by pre-stimulus abnormalities across multiple frequencies, then early high-frequency abnormalities followed by low-frequency abnormalities. Increased pre-stimulus activity was a ‘core’ abnormality, with pre-stimulus activity predicting post-stimulus neural abnormalities, group membership, and clinical symptoms (CELF-4 Core Language Index). Deficits in synaptic integration in the auditory cortex are associated with oscillatory abnormalities in ASD as well as patient symptoms. Increased pre-stimulus activity in ASD likely demonstrates a fundamental signal-to-noise deficit in individuals with ASD, with elevations in oscillatory activity suggesting an inability to maintain an appropriate ‘neural tone’ and an inability to rapidly return to a resting state prior to the next stimulus.